VATS lobectomy for early lung cancer: long-term outcomes - Toste, Paul A.; Lee, Jay M. (Annals of Translational Medicine, 2019)
Historically, the mainstay of treatment for early-stage lung cancer has been anatomic resection via thoracotomy. Over the last two decades, there has been increasing adoption of video-assisted thoracoscopic surgery (VATS) techniques in this group of patients. VATS resection has been shown to reduce perioperative morbidity and hospital length of stay in multiple series (1-8). Perioperative mortality has also been shown to be lower or equivalent (1-7). While data is limited, several small studies have demonstrated similar survival and recurrence rates with VATS compared to open resection for early-stage lung cancer (9-11).